Defect structures in B[subscript]12As[subscript]2 epitaxial layers grown on (0001) 6H-SiC - Chen, H.; Wang, G.; Dudley, M.; Zhang, L.; Wu, L.; Zhu, Y.; Xu, Z.; Edgar, James H.; Kuball, M. (My University, 2008)
A detailed analysis of the microstructure in B12[subscript]As[subscript]2 epitaxial layers grown by chemical-vapor deposition on (0001) 6H-SiC substrates is presented. Synchrotron white beam x-ray topography enabled macroscopic characterization of the substrate/epilayer ensembles and revealed the presence of a quite homogeneous solid solution of twin and matrix epilayer domains forming a submicron mosaic structure. The basic epitaxial relationship was found to be (0001)(B12[subscript]As[subscript]2) < 1120 >(B12[subscript]As[subscript]2) parallel to(0001)(6H-SiC) < 1120 >(6H-SiC) and the twin relationship comprised a 180 degrees (or equivalently 60 degrees) rotation about [0001](B12[subscript]As[subscript]2) in agreement with previous reports. Cross-sectional high resolution transmission electron microscopy revealed the presence of a similar to 200 nm thick disordered transition layer which was shown to be created by the coalescence of a mosaic of translationally and rotationally variant domains nucleated at various types of nucleation sites available on the (0001) 6H-SiC surface. In this transition layer, competition between the growth of the various domains is mediated in part by the energy of the boundaries created between them as they coalesce. Boundaries between translationally variant domains are shown to have unfavorable bonding configurations and hence high-energy. These high-energy boundaries can be eliminated during mutual overgrowth by the generation of a 1/3[0001](B12[subscript]As[subscript]2) Frank partial dislocation which effectively eliminates the translational variants. This leads to an overall improvement in film quality beyond thicknesses of similar to 200 nm as the translational variants grow out leaving only the twin variants. (0003) twin boundaries in the regions beyond 200 nm are shown to possess fault vectors such as 1/6[1100](B12[subscript]As[subscript]2), which are shown to originate from the mutual shift between the nucleation sites of the respective domains.
Keywords: Boron-rich solids; Cemical vapor deposition; Thin films; Heteroepitaxial growth; Variants